2016
DOI: 10.1097/coh.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

What people want from sex and preexposure prophylaxis

Abstract: Current PrEP implementation provides direct and indirect benefits that are highly desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 53 publications
5
59
0
Order By: Relevance
“…PrEP offers an HIV prevention strategy that places control into the hands of its users, specifically sex workers themselves in our context. These findings are similar to other studies that have found that PrEP use increases a feeling of safety and empowerment during sex [38]. The data from the feasibility study shows the readiness, willingness, and strong desire for a PrEP demonstration project.…”
Section: Discussionsupporting
confidence: 89%
“…PrEP offers an HIV prevention strategy that places control into the hands of its users, specifically sex workers themselves in our context. These findings are similar to other studies that have found that PrEP use increases a feeling of safety and empowerment during sex [38]. The data from the feasibility study shows the readiness, willingness, and strong desire for a PrEP demonstration project.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, our results reinforce and expand on previous studies that have started to demonstrate the individual positive outcomes of PrEP use beyond biomedical outcomes (Grant & Koester, 2016). For instance, previous qualitative research reported relief from stress and fear associated with PrEP use among participants in clinical trials, substance-using men who have sex with men (MSM), and MSM in Seattle (Collins et al, 2017;Koester et al, 2017;Storholm et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…PrEP use has been associated with feelings of empowerment, agency and safety during sex, and partners’ honesty in sharing their HIV status [18]. Data from LMIC are limited.…”
Section: Discussionmentioning
confidence: 99%